2014
DOI: 10.1007/s11262-014-1142-0
|View full text |Cite
|
Sign up to set email alerts
|

Recombination analysis of Maize dwarf mosaic virus (MDMV) in the Sugarcane mosaic virus (SCMV) subgroup of potyviruses

Abstract: Recombination among RNA viruses is a natural phenomenon that appears to have played a significant role in the species development and the evolution of many strains. It also has particular significance for the risk assessment of plants which have been genetically modified for disease resistance by incorporating viral sequences into their genomes. However, the exact recombination events taking place in viral genomes are not investigated in detail for many virus groups. In this analysis, different single-stranded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
1
15
0
1
Order By: Relevance
“…Subsequently, further spread of SCMV within Iran could have occurred via movement of contaminated vegetative cuttings across provinces to other host plants such as maize, sorghum, and so on and within provinces via aphid vectors. Mutation and recombination are two main sources of genetic variation in RNA viruses (Gell et al, 2015; Mangrauthia et al, 2008; Moreno et al, 2004; Padhi and Ramu, 2011). Recombination events are common in Potyvirus evolution and can be detected throughout the genome (Chare and Holmes, 2006; Revers et al, 1996; Sztuba-Solińska et al, 2011; Valli et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, further spread of SCMV within Iran could have occurred via movement of contaminated vegetative cuttings across provinces to other host plants such as maize, sorghum, and so on and within provinces via aphid vectors. Mutation and recombination are two main sources of genetic variation in RNA viruses (Gell et al, 2015; Mangrauthia et al, 2008; Moreno et al, 2004; Padhi and Ramu, 2011). Recombination events are common in Potyvirus evolution and can be detected throughout the genome (Chare and Holmes, 2006; Revers et al, 1996; Sztuba-Solińska et al, 2011; Valli et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As SCSMV can be transmitted through vegetative set, it seems that Iranian isolates have been introduced into the country from sugarcane-producing Asian countries such as India and Pakistan via contaminated vegetative cuttings. In RNA viruses, viral genome evolutions are directed by recombination and mutation events, which are two important sources of genetic variation (Roossinck, 1997;Posada et al, 2002;Gell et al, 2015). Recombination occurs frequently among members of the family Potyviridae (Revers et al, 1996;Chare and Holmes, 2006;Valli et al, 2007;Padhi and Ramu, 2011;Sztuba-Solin' ska et al, 2011;Gell et al, 2015), however, no recombination event was found in Iranian SCSMV isolates and also other members of group II, suggesting that probably this evolutionary force has not shaped the emergence of SCSMV group II variants (in contrast to group I (Liang et al, 2016)).…”
Section: Discussionmentioning
confidence: 99%
“…Owing to this deletion the CP of the Indian isolates is 266 amino acids instead of 267 as in case of all other isolates. In case of RNA viruses it is a well‐known fact that the virus populations may be variable within a given plant because of the constant occurrence of replication errors leading to changes, mutations and recombination (Gell, ). Although there was no recombination event detected in the Indian isolates (analyzed by RDP3; Martin et al , ), this missing triplet could be a result of a deletion which has been selected in nature and is being passed on to further generations, probably suited to virus multiplication in this Hwc and bamboo (Awasthi et al , ).…”
Section: Discussionmentioning
confidence: 99%